Characteristics of Diagnosed Concussions in Children Aged 0 to 4 Years Presenting to a Large Pediatric Healthcare Network. Issue 12 (December 2021) - Podolak, Olivia E.; Chaudhary, Sofia; Haarbauer-Krupa, Juliet; Metzger, Kristina B.; Curry, Allison E.; Kessler, Ronni S.; Pfeiffer, Melissa R.; Breiding, Matthew J.; Master, Christina L.; Arbogast, Kristy B.
Abstract : Objective: The aim of the study was to comprehensively describe the natural history of concussion in early childhood between 0 and 4 years. Methods: Retrospective cohort study of 329 patients aged 0 to 4 years, with an International Classification of Diseases, Ninth Revision, concussion diagnosis in the Children's Hospital of Philadelphia healthcare network from October 1, 2013, to September 30, 2015. Clinical data were abstracted from the Children's Hospital of Philadelphia electronic health record, which captured all clinical care visits and injury characteristics. Results: Nearly 9 (86.6%) of 10 patients sought care in the emergency department or urgent care setting, most commonly on the day of injury (56.2%) and as a result of a fall (64.4%). More than two-thirds (64.4%) of patients or their parent/caregiver reported somatic symptoms (ie, vomiting or headache), whereas close to half (49.2%) reported sleep issues. One of 5 patients identified emotional symptoms (21.9%) or visio-vestibular dysfunction (20.4%). Many patients also experienced symptoms not included in standard assessment tools including personality changes (34.0%) and change in appetite (12.8%). Conclusions: These results provide insight into the clinical characteristics of concussion in early childhood up to 4 years of age. Because assessment in this group relies heavily on parent/caregiver symptom reporting, rather than patient self-report, these results will aid clinicians with the challenge of diagnosing concussions in this population. These findings highlight the need to develop additional tools to adequately and systematically assess common signs and symptoms of concussion in early childhood that may not be included in standard assessment scales routinely used in older adolescents and adults.